Ethics & Technology : Ethical Issues in an Age of Information and Communication Technology - Tavani, Herman T. (John Wiley & Sons, 2007)
Offering thought-provoking insights and up-to-date coverage of the rapidly expanding field of cyberethics, this new book introduces readers to current issues in computer ethics. The author, a respected authority on the subject, combines his years of experience in the field with balanced coverage of concepts and real-world case studies.